1996
DOI: 10.1074/jbc.271.15.8709
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Antigen Receptor Ubiquitination Is a Consequence of Receptor-mediated Tyrosine Kinase Activation

Abstract: Engagement of the T cell antigen receptor results in both its phosphorylation and its ubiquitination. T cell antigen receptor ubiquitination was evaluated in Jurkat, a well characterized human T leukemia cell line. Treatment of cells with the tyrosine kinase inhibitor herbimycin A resulted in an inhibition of receptor ubiquitination. Consistent with this, pervanadate, which increases cellular tyrosine phosphorylation, enhanced receptor ubiquitination. A requirement for receptormediated tyrosine kinase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 59 publications
2
52
0
1
Order By: Relevance
“…Among the immunoreceptors, the T cell receptor undergoes phosphory- lation-dependent ubiquitination (19), possibly also involving Cbl. Interestingly, expression of a constitutively active form of p56lck causes internalization and lysosomal degradation of the assembled cell surface T cell receptors (20).…”
Section: Resultsmentioning
confidence: 99%
“…Among the immunoreceptors, the T cell receptor undergoes phosphory- lation-dependent ubiquitination (19), possibly also involving Cbl. Interestingly, expression of a constitutively active form of p56lck causes internalization and lysosomal degradation of the assembled cell surface T cell receptors (20).…”
Section: Resultsmentioning
confidence: 99%
“…Lck is required for the TCR to be ubiquitinated and degraded following TCR engagement (27). Because c-Cbl functions as a ubiquitin ligase, resulting in targeting of tyrosine-phosphorylated receptors for endocytosis and degradation (23,24), and inactivation of c-Cbl results in up-regulation of TCR expression in immature DP thymocytes that normally have a TCR low phenotype (21,22), we hypothesized that c-Cbl could be involved in maintenance of ␣-chain phenotypic allelic exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of cell surface receptors is an endocytotic signal that can target them for degradation in proteosomes or by lysosomes (25). This suggested that c-Cbl could be involved in endocytosis and/or degradation of TCR after activation, because ubiquitination of TCR occurs after TCR-mediated stimulation and requires Lck activity (26,27). Recent data confirm that c-Cbl and its close relative Cbl-b are closely involved in the down-modulation and degradation of TCR after activation (28).…”
mentioning
confidence: 99%
“…Anti-CD3-␦ (R9) (17); antiubiquitin (18); and anti-TCR-␣, H28 (19) have all been described. Anti-HA (12CA5) and anti-Myc (9E10) monoclonal antibodies were from culture supernatants.…”
Section: Methodsmentioning
confidence: 99%